2016
DOI: 10.1001/jamadermatol.2016.0225
|View full text |Cite
|
Sign up to set email alerts
|

Hair and Nail Changes During Long-term Therapy With Ibrutinib for Chronic Lymphocytic Leukemia

Abstract: Importance Ibrutinib (Imbruvica®), a Bruton tyrosine kinase (BTK) inhibitor, is a new targeted agent approved by the US Food and Drug Administration for the treatment of chronic lymphocytic leukemia (CLL), mantle cell lymphoma, and Waldenström macroglobulinemia. Ibrutinib is overall well-tolerated but requires long-term treatment until disease progression or intolerable toxicity occurs. Little is known regarding its cutaneous adverse effects. Objective To describe the hair and nail manifestations associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 15 publications
(22 reference statements)
1
43
1
Order By: Relevance
“…Dermatological toxicities have also been reported in 2-27% of treated patients (Ransohoff & Kwong, 2017;Iberri et al, 2018), mainly mild-to-moderate rash, neutrophilic panniculitis, progressive hair and nail changes, skin infections, bruising, petechiae and purpuric eruption (Fabbro et al, 2015;Bitar et al, 2016;Ransohoff & Kwong, 2017;Iberri et al, 2018). In contrast, oral toxicity with ibrutinib has rarely been described.…”
mentioning
confidence: 99%
“…Dermatological toxicities have also been reported in 2-27% of treated patients (Ransohoff & Kwong, 2017;Iberri et al, 2018), mainly mild-to-moderate rash, neutrophilic panniculitis, progressive hair and nail changes, skin infections, bruising, petechiae and purpuric eruption (Fabbro et al, 2015;Bitar et al, 2016;Ransohoff & Kwong, 2017;Iberri et al, 2018). In contrast, oral toxicity with ibrutinib has rarely been described.…”
mentioning
confidence: 99%
“…In contrast, oral toxicity with ibrutinib has rarely been described. A prospective dermatological survey did not observe any mucosal involvement in a cohort of 66 consecutive patients (Bitar et al , ). However, a recent pivotal study reported all‐grade and high‐grade stomatitis in 11% and 1% of treated patients, respectively, but the clinical aspects were not documented (Byrd et al , ).…”
Section: Clinical Features Of Chronic Lymphocytic Leukaemia Patients mentioning
confidence: 97%
“…However, the rate of grade ≥3 adverse events remains low and treatment discontinuation due to toxicity (Byrd et al , , ) is uncommon and mostly related to infections (Byrd et al , , ; Burger et al , ; Puła et al , ; Tran & O'Brien, ). Dermatological toxicities have also been reported in 2–27% of treated patients (Ransohoff & Kwong, ; Iberri et al , ), mainly mild‐to‐moderate rash, neutrophilic panniculitis, progressive hair and nail changes, skin infections, bruising, petechiae and purpuric eruption (Fabbro et al , ; Bitar et al , ; Ransohoff & Kwong, ; Iberri et al , ). In contrast, oral toxicity with ibrutinib has rarely been described.…”
Section: Clinical Features Of Chronic Lymphocytic Leukaemia Patients mentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Brittle nails and textural hair changes have been reported during long-term therapy of CLL with ibrutinib, but the underlying mechanisms remain unknown. [86]…”
Section: Safety Tolerability Toxicity and Potential Off-targetmentioning
confidence: 99%